Multi-locus typing scheme for Babesia bovis and Babesia bigemina reveals high levels of genetic variability in strains from Northern Argentina - Guillemi, Eliana Carolina (2013)
Bovine babesiosis, caused by the protozoa Babesia bovis and Babesia bigemina, is a tick-borne disease distributed in tropical regions worldwide. Current control measures are based on the use of acaricides and live attenuated vaccines. The major economic impact of babesiosis lies in the cattle industry. In order to gain insight into the extent of genetic diversity in populations of parasites in the field, we developed two MLST schemes for the molecular genotyping of B. bigemina and B. bovis. We have also developed a custom-designed bioinformatic pipeline to facilitate the automated processing of raw sequences and further diversity and phylogenetic analysis. The overall MLST scheme exhibited the maximum discriminatory power (Simpson Index = 1) for B. bovis and a high level of discrimination for B. bigemina(Simpson Index = 0.9545). Genetic diversity was very high and infections with multiple genotypes were frequently found for both parasites in outbreak samples from the Northeast and Northwest of Argentina. Recombination events, which could have arisen from these multiple infections, were suggested by intra-loci linkage disequilibrium analysis and the lack of congruence in phylogenetic trees from individual genes. The two MLST schemes developed here are a robust, objective and easily adoptable technology to analyze the genetic diversity and population structure of parasites of the genus Babesia.